PREHOSPITALIZED MANAGEMENT ON ACUTE STROKE - Narakusuma Wirawan; Ida Bagus Kusuma Putra (Universitas Udayana, 2013)
The general purpose in stroke management is to decrease the morbidity and mortality case and also to decrease the disability. One of the effort that have important role to reach the goal is early identification the sign of stroke and early prahospitalized management on the right time. One easy method that could be use is FAST method. FAST method is a screening tool for the patient to know the abnormality in facial muscle, weakness of the limbs and the speech disturbance, provide the early identification of the stroke that easy to understand and applicable in society. With this methode, hopefully the society can act fast and understand about the early sign of the stroke and rapidly send the pasient to the nerby medical center or call the ambulance.